State of the art applications of biotechnology in wastewater treatment. - Jose, Wilfredo I.
Biological waste treatment processes such as the activated sludge and biomethanation use naturally occuring microorganisms. With environmental biotechnology, the performance of these processes can be improved. Special strains can be isolated to treat xenobiotics and other poorly degradable substances found in municipal sewage and industrial wastes.